Groundwater contamination and health risk evaluation of naturally occurring potential toxic metals of Hatiya Island, Bangladesh - Rahman, Mahfuzur; Islam Khan, Md. Sadril; Hossain, Mohammad Sabbir; Hossain, Md. Imam Shohel; Hasan, Mahmudul; Hamli, Hadi; Mustafa, M. Golam (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
Groundwater meets the majority portion of drinking water needs, particularly in the rural area of Bangladesh. Groundwater has been continuously contaminated by potentially harmful metals as a result of natural processes as well as some anthropogenic activity, creating a variety of health impacts. The current research aimed to evaluate the naturally occurring level of metal contamination and the human health risk associated with deep groundwater in the Hatiya Island. Because of the arsenic, iron, and salinity problem in shallow groundwater, the inhabitants of the Hatiya Island use deep groundwater. During the field investigation, no shallow tubewells were observed; therefore, only deep groundwater samples were collected. The total sample size collected throughout the Hatiya island was 17. Five metals (Zn, Fe, Mg, Mn, and Cu) were analyzed using an Atomic Absorption Spectrophotometer (AAS). The concentrations of studied potential risky metals were ranked as follows: Mg > Zn > Fe >Mn> Cu. The detected values of all metals except Fe were found within the drinking water limits of WHO (2017), BIS (2012), and BDWS (1997), where only 29.41% of the Fe sample exceeded the standard drinking limits. According to the metal evaluation index (MEI) and degree of contamination (Cd), the groundwater of the study area is free from contamination but the metal pollution index (MPI) and nemerow pollution index (NI) exhibited little pollution in the middle of the western part of the study area. The hazard quotient (HQ) values revealed no oral and dermal health risk for individual metals (Cu, Zn, Fe, Mn). On the other hand, the hazard index (HI) values exhibited no risk for combined metals as none of the values exceeded the safety limit value of 1. According to the HQ and HI results, the deep groundwater on Hatiya Island is non-carcinogenic and risk-free for children and adults. However, children were more susceptible to oral health risks than adults. In contrast, adults were more vulnerable to dermal health risks than children.